LuNER: Multiplexed SARS-CoV-2 detection in clinical swab and wastewater samples - Stahl, Elizabeth C.; Gopez, Allan R.; Tsuchida, Connor A.; Fan, Vinson B.; Moehle, Erica A.; Witkowsky, Lea B.; Hamilton, Jennifer R.; Lin-Shiao, Enrique; McElroy, Matthew; McDevitt, Shana L.; Ciling, Alison; Tsui, C. Kimberly; et al. (PloS one, 2021)
Clinical and surveillance testing for the SARS-CoV-2 virus relies overwhelmingly on RT-qPCR-based diagnostics, yet several popular assays require 2–3 separate reactions or rely on detection of a single viral target, which adds significant time, cost, and risk of false-negative results. Furthermore, multiplexed RT-qPCR tests that detect at least two SARS-CoV-2 genes in a single reaction are typically not affordable for large scale clinical surveillance or adaptable to multiple PCR machines and plate layouts. We developed a RT-qPCR assay using the Luna Probe Universal One-Step RT-qPCR master mix with publicly available primers and probes to detect SARS-CoV-2 N gene, E gene, and human RNase P (LuNER) to address these shortcomings and meet the testing demands of a university campus and the local community. This cost-effective test is compatible with BioRad or Applied Biosystems qPCR machines, in 96 and 384-well formats, with or without sample pooling, and has a detection sensitivity suitable for both clinical reporting and wastewater surveillance efforts.